Clinically compatible subject-specific dynamic parallel transmit pulse design for homogeneous fat saturation and water-excitation at 141657T: Proof-of-concept for 14165CEST MRI of the brain - Levy, Simon; Herrler, Jürgen; Liebert, Andrzej; Tkotz, Katharina; Fabian, Moritz; Eisen, Christian; Grodzki, David; Uder, Michael; Dörfler, Arnd; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the benefits and challenges of dynamic parallel transmit (pTx) pulses for fat saturation (FS) and water-excitation (WE), in the context of CEST MRI. Methods "Universal" k(T)-points (for FS) and spiral non-selective (for WE) trajectories were optimized offline for flip angle (FA) homogeneity. Routines to optimize the pulse shape online, based on the subject's fields maps, were implemented (target FA of 110 degrees/0 degrees for FS, 0 degrees/5 degrees for WE at fat/water frequencies). The pulses were inserted in a CEST sequence with a pTx readout. The different fat suppression schemes and their effects on CEST contrasts were compared in 12 volunteers at 7T. Results With a 25%-shorter pulse duration, pTx FS largely improved the FA homogeneity (root-mean-square-error (RMSE) = 12.3 degrees vs. 53.4 degrees with circularly-polarized mode, at the fat frequency). However, the spectral selectivity was degraded mainly in the cerebellum and close to the sinuses (RMSE = 5.8 degrees vs. 0.2 degrees at the water frequency). Similarly, pTx WE showed a trade-off between FA homogeneity and spectral selectivity compared to pTx non-selective pulses (RMSE = 0.9 degrees and 1.1 degrees at the fat and water frequencies, vs. 4.6 degrees and 0.5 degrees). In the brain, CEST metrics were reduced by up to 31.9% at -3.3 ppm with pTx FS, suggesting a mitigated lipid-induced bias. Conclusion This clinically compatible implementation of dynamic pTx pulses improved the fat suppression homogeneity at 7T taking into account the subject-specific B-0 heterogeneities online. This study highlights the lipid-induced biases on the CEST z-spectrum. The results are promising for body applications where B-0 heterogeneities and fat are more substantial.
CRIS-Team WoS Importer:2022-09-30

Multi-echo–based fat artifact correction for CEST MRI at 7 T - Tkotz, Katharina; Liebert, Andrzej; Gast, Lena; Zeiger, Paula; Uder, Michael; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2024)
Purpose: CEST MRI is influenced by fat signal, which can reduce the apparent CEST contrast or lead to pseudo-CEST effects. Our goal was to develop a fat artifact correction based on multi-echo fat–water separation that functions stably for 7 T knee MRI data. Methods: Our proposed algorithm utilizes the full complex data and a phase demodulation with an off-resonance map estimation based on the Z-spectra prior to fat–water separation to achieve stable fat artifact correction. Our method was validated and compared to multi-echo–based methods originally proposed for 3 T by Bloch–McConnell simulations and phantom measurements. Moreover, the method was applied to in vivo 7 T knee MRI examinations and compared to Gaussian fat saturation and a published single-echo Z-spectrum–based fat artifact correction method. Results: Phase demodulation prior to fat–water separation reduced the occurrence of fat–water swaps. Utilizing the complex signal data led to more stable correction results than working with magnitude data, as was proposed for 3 T. Our approach reduced pseudo-nuclear Overhauser effects compared to the other correction methods. Thus, the mean asymmetry contrast at 3.5 ppm in cartilage over five volunteers increased from −9.2% (uncorrected) and −10.6% (Z-spectrum–based) to −1.5%. Results showed higher spatial stability than with the fat saturation pulse. Conclusion: Our work demonstrates the feasibility of multi-echo–based fat–water separation with an adaptive fat model for fat artifact correction for CEST MRI at 7 T. Our approach provided better fat artifact correction throughout the entire spectrum and image than the fat saturation pulse or Z-spectrum–based correction method for both phantom and knee imaging results.
CRIS-Team Scopus Importer:2023-12-08
Keywords: 7 T; CEST; fat artifact; fat–water separation; knee imaging; nuclear Overhauser effect

Parameter optimization for proton density fat fraction quantification in skeletal muscle tissue at 7 T - Tkotz, Katharina; Zeiger, Paula; Hanspach, Jannis; Mathy, Claudius; Laun, Frederik Bernd; Uder, Michael; Nagel, Armin Michael; Gast, Lena (Magnetic Resonance Materials in Physics Biology and Medicine, 2024)
Objective: To establish an image acquisition and post-processing workflow for the determination of the proton density fat fraction (PDFF) in calf muscle tissue at 7 T. Materials and methods: Echo times (TEs) of the applied vendor-provided multi-echo gradient echo sequence were optimized based on simulations of the effective number of signal averages (NSA*). The resulting parameters were validated by measurements in phantom and in healthy calf muscle tissue (n = 12). Additionally, methods to reduce phase errors arising at 7 T were evaluated. Finally, PDFF values measured at 7 T in calf muscle tissue of healthy subjects (n = 9) and patients with fatty replacement of muscle tissue (n = 3) were compared to 3 T results. Results: Simulations, phantom and in vivo measurements showed the importance of using optimized TEs for the fat–water separation at 7 T. Fat–water swaps could be mitigated using a phase demodulation with an additional B0 map, or by shifting the TEs to longer values. Muscular PDFF values measured at 7 T were comparable to measurements at 3 T in both healthy subjects and patients with increased fatty replacement. Conclusion: PDFF determination in calf muscle tissue is feasible at 7 T using a chemical shift-based approach with optimized acquisition and post-processing parameters.
CRIS-Team Scopus Importer:2024-08-16
Keywords: 7 Tesla; Dixon MRI; Fat–water separation (FWS); Proton density fat fraction (PDFF); Skeletal muscle tissue

Super-Resolution for CEST MRI - Folle, Lukas; Tkotz, Katharina; Liebert, Andrzej; Gadjimuradov, Fasil; Kapsner, Lorenz; Fabian, Moritz; Bickelhaupt, Sebastian; Simon, David; Kleyer, Arnd; Krönke, Gerhard; Roemer, Frank; Zaiß, Moritz; et al. (Joint annual meeting ISMRM-ESMRMB ISMRT, 2022)
The resolution of chemical exchange saturation transfer (CEST) magnetic resonance imaging is limited by physical constraints. To visualize metabolic processes of small structures using CEST in patients knees, an increased resolution is necessary. In this work, we compared trilinear interpolation and zero-filling to neural network-based approaches to estimate a high-resolution image given the corresponding low-resolution data. We could show that a substantial quantitative improvement using neural networks could be achieved for unsaturated images while maintaining a comparable CEST contrast. Generalization of the method to brain CEST MRI was achieved without retraining of the networ
Keywords: MRI; Super-resolution

Towards Super-resolution CEST MRI for Visualization of Small Structures - Folle, Lukas; Tkotz, Katharina; Gadjimuradov, Fasil; Kapsner, Lorenz; Fabian, Moritz; Bickelhaupt, Sebastian; Simon, David; Kleyer, Arnd; Krönke, Gerhard; Zaiß, Moritz; Nagel, Armin Michael; Maier, Andreas (Bildverarbeitung für die Medizin 2022, 2022)
The onset of rheumatic diseases such as rheumatoid arthritis is typically subclinical, which results in challenging early detection of the disease. However, characteristic changes in the anatomy can be detected using imaging techniques such as MRI or CT. Modern imaging techniques such as chemical exchange saturation transfer (CEST) MRI drive the hope to improve early detection even further through the imaging of metabolites in the body. To image small structures in the joints of patients, typically one of the first regions where changes due to the disease occur, a high resolution for the CEST MR imaging is necessary. Currently, however, CEST MR suffers from an inherently low resolution due to the underlying physical constraints of the acquisition. In this work we compared established up-sampling techniques to neural network-based super-resolution approaches. We could show, that neural networks are able to learn the mapping from low-resolution to high-resolution unsaturated CEST images considerably better than present methods. On the test set a PSNR of 32.29 dB (+10%), a NRMSE of 0.14 (+28%), and a SSIM of 0.85 (+15%) could be achieved using a ResNet neural network, improving the baseline considerably. This work paves the way for the prospective investigation of neural networks for super-resolution CEST MRI and, followingly, might lead to a earlier detection of the onset of rheumatic diseases.
Keywords: Deep Learning; Rheumatic diseases; Reconstruction

Whole-brain quantitative CEST MRI at 7T using parallel transmission methods and B1+ correction - Liebert, Andrzej; Tkotz, Katharina; Herrler, Jürgen; Linz, Peter; Mennecke, Angelika; German, Alex; Liebig, Patrick; Gumbrecht, Rene; Schmidt, Manuel; Dörfler, Arnd; Uder, Michael; Zaiß, Moritz; et al. (Magnetic Resonance in Medicine, 2021)
Purpose: To enable whole-brain quantitative CEST MRI at ultra-high magnetic field strengths (B0 ≥ 7T) within short acquisition times. Methods: Multiple interleaved mode saturation (MIMOSA) was combined with fast online-customized (FOCUS) parallel transmission (pTx) excitation pulses and (Formula presented.) correction to achieve homogenous whole-brain coverage. Examinations of 13 volunteers were performed on a 7T MRI system with 3 different types of pulse sequences: (1) saturation in circular polarized (CP) mode and CP mode readout, (2) MIMOSA and CP readout, and (3) MIMOSA and FOCUS readout. For comparison, the inverse magnetic transfer ratio metric for relayed nuclear Overhauser effect and amide proton transfer were calculated. To investigate the number of required acquisitions for a good (Formula presented.) correction, 4 volunteers were measured with 6 different B1 amplitudes. Finally, time point repeatability was investigated for 6 volunteers. Results: MIMOSA FOCUS sequence using (Formula presented.) correction, with both single and multiple points, reduced inhomogeneity of the CEST contrasts around the occipital lobe and cerebellum. Results indicate that the most stable inter-subject coefficient of variation was achieved using the MIMOSA FOCUS sequence. Time point repeatability of MIMOSA FOCUS with single-point (Formula presented.) correction showed a maximum coefficient of variation below 8% for 3 measurements in a single volunteer. Conclusion: A combination of MIMOSA FOCUS with a single-point (Formula presented.) correction can be used to achieve quantitative CEST measurements at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced as additional scans required for (Formula presented.) correction can be omitted.
CRIS-Team Scopus Importer:2021-03-12
Keywords: 7T; chemical exchange saturation transfer; fast-online customized pulses; multiple interleaved mode saturation; parallel transmission; spiral non-selective trajectory